Defect Prediction at The Superplastic Forming Process of The Bipolar Plate by Simulation - Choirotin, Ismi; Choiron, Moch. Agus (Journal of Energy, Mechanical, Material and Manufacturing Engineering, 2018)
Â Improper parameter setting at the bipolar plate forming by superplastic process will outcome damage to the final workpiece. By employing computer simulation, the defect at the bipolar plate could be predicted close to the maximum thickness reduction and the effective stress data. Simulate the fabrication of bipolar plate by a number of forming temperature (350 â 450 Â°C) and air pressure (0.25 â 1 MPa) utilize Ansys, resulting maximum thickness reduction and effective stress occurred at 450 Â°C and 1 MPa. Make reference to the result, the bipolar plate didnât expose any deficiency with 36.75% maximum thickness reduction. Have recourse to simulation will abbreviate the trial and error method as of the production process will more effective and efficient in terms of time and cost